AKUNTABILITAS DAN PENGELOLAAN KEUANGAN MASJID MELALUI PENDEKATAN FENOMENOLOGI (STUDI KASUS PADA YAYASAN MASJID BAITURRAHMAN PAKUSARI - JEMBER) - Kamilia, Ibna; Pujiarti, Pujiarti (Jurnal Ilmiah Akuntansi Indonesia, 2017)
Abstract: This research shows that the importance of accountability in financial statements. The objectives to be achieved, namely to look on the side of the financial statements at the Baiturrahman mosque has been appropriate or not in accordance with the applicable standard. This research uses descriptive qualitative approach to Phenomenology. Phenomenology of approach used to understand in depth the activity to finance existing in the mosque of Baiturrahman Pakusari, Jember. These studies gain exposure of accountability both for their fellow human beings as well as accountability to God Almighty, in accordance with the understanding and the fact that in the natural by stewards. With regard to the financial statements, the mosque of Baiturrahman Pakusari, Jember still do not meet the financial statement components in accordance with PSAK Number 45. At the Baiturrahman Mosque just present the report simply because of limited human resources. So, researcher makes financial statements that comply with the PSAK Number 45 of document that researchers get. Keywords :?Accountability, Financial Statements, PSAK Number 45, The Phenomenology of Approach